SIRT1 Positively Regulates Autophagy and Mitochondria Function in Embryonic Stem Cells Under Oxidative Stress. (17th April 2014) - Ou, Xuan; Lee, Man Ryul; Huang, Xinxin; Messina‐Graham, Steven; Broxmeyer, Hal E.
Abstract: SIRT1, an NAD‐dependent deacetylase, plays a role in regulation of autophagy. SIRT1 increases mitochondrial function and reduces oxidative stress, and has been linked to age‐related reactive oxygen species (ROS) generation, which is highly dependent on mitochondrial metabolism. H2 O2 induces oxidative stress and autophagic cell death through interference with Beclin 1 and the mTOR signaling pathways. We evaluated connections between SIRT1 activity and induction of autophagy in murine (m) and human (h) embryonic stem cells (ESCs) upon ROS challenge. Exogenous H2 O2 (1 mM) induced apoptosis and autophagy in wild‐type (WT) and Sirt1−/− mESCs. High concentrations of H2 O2 (1 mM) induced more apoptosis in Sirt1−/−, than in WT mESCs. However, addition of 3‐methyladenine, a widely used autophagy inhibitor, in combination with H2 O2 induced more cell death in WT than in Sirt1−/− mESCs. Decreased induction of autophagy in Sirt1−/− mESCs was demonstrated by decreased conversion of LC3‐I to LC3‐II, lowered expression of Beclin‐1, and decreased LC3 punctae and LysoTracker staining. H2 O2 induced autophagy with loss of mitochondrial membrane potential and disruption of mitochondrial dynamics in Sirt1−/− mESCs. Increased phosphorylation of P70/85‐S6 kinase and ribosomal S6 was noted in Sirt1−/− mESCs, suggesting that SIRT1 regulates the mTOR pathway. Consistent with effects in mESCs, inhibition of SIRT1 using Lentivirus ‐mediated SIRT1 shRNA in hESCs demonstrated that knockdown of SIRT1 decreased H2 O2 ‐induced autophagy. This suggests a role for SIRT1 in regulating autophagy and mitochondria function in ESCs upon oxidative stress, effects mediated at least in part by the class III PI3K/Beclin 1 and mTOR pathways. Stem Cells   2014;32:1183–1194